GERAKAN PRAMUKA SEBAGAI SARANA PEMBENTUKAN KARAKTER DISIPLIN, MANDIRI, DAN RELIGIUS SEKOLAH MENENGAH PERTAMA (SMP) - Setyabudi, Muhammad Rizky; Rahayu, Qonita Nur Aeni; Aulia, Shafa; Famularsih, Sari; Anggrain, Rosmawati Yustika; Asy’syakurni, Nurul Afdhilla (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
The Scout Movement plays a strategic role as a vehicle for character education at the junior high school level, particularly in internalizing the values of discipline, independence, and religiosity. This study examines the effectiveness of scouting activities at SMP Negeri 4 Salatiga, which combine weekly routine training and camping activities as a holistic development method for students in grades VII, VIII, and IX. The main focus of the study lies in the implementation of the